Green bonds for financing renewable energy and energy efficiency in South-East Asia: a review of policies. (2nd April 2020) - Azhgaliyeva, Dina; Kapoor, Anant; Liu, Yang
ABSTRACT: Mobilizing private finance for renewable energy and energy efficiency is critical for Association of South-East Asian Nations (ASEAN) not only for the reduction of global temperature rise but also for meeting fast-growing energy demand. Two-thirds of green bonds issued in ASEAN were used to finance renewable energy and energy efficiency projects. This paper provides a review of green bond issuance and green bond policies in ASEAN. Issuance of green bonds in top three green bond issuing countries in ASEAN, i.e. Indonesia, Malaysia and Singapore, are reviewed in detail. Green bond policies in ASEAN are effective in promoting green bond issuance. However, this does not mean that green bond policies are effective in promoting renewable energy and energy efficiency projects in ASEAN. Proceedings of green bonds issued in ASEAN can be used for financing projects abroad or re-financing past loans, thus do not necessarily promote green investments in ASEAN.